2019
DOI: 10.1080/21691401.2019.1601101
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of AURKA polymorphisms with smoking on the susceptibility of oral cancer

Abstract: Objective: The objective of this study was aimed to investigate the interactions between Aurora kinase A (AURKA) gene polymorphisms (T91A and G169A) and smoking and their effects on the susceptibility of oral cancer. Methods: One hundred five healthy controls were frequency-matched with 91 oral cancer patients by age, sex and nationality. Detection of AURKA T91A and G169A polymorphisms was performed using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. Differences in genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“… 72 Meanwhile, AURKA is highly expressed in a variety of human cancers, including breast cancer, 73 lung cancer, 74 gastrointestinal cancer, 75 bladder cancer, 76 and oral cancer. 77 A study demonstrated that genetic variations in AURKA might be a reliable predictor of early-stage HCC and a crucial biomarker for HCC development. 78 Moreover, other research has indicated that AURKA contributes in metastasis and invasiveness of HCC.…”
Section: Discussionmentioning
confidence: 99%
“… 72 Meanwhile, AURKA is highly expressed in a variety of human cancers, including breast cancer, 73 lung cancer, 74 gastrointestinal cancer, 75 bladder cancer, 76 and oral cancer. 77 A study demonstrated that genetic variations in AURKA might be a reliable predictor of early-stage HCC and a crucial biomarker for HCC development. 78 Moreover, other research has indicated that AURKA contributes in metastasis and invasiveness of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors are involved in the pathogenesis of oral cancer ( Gharat et al, 2016 ). External factors including smoking ( Huang et al, 2019 ), drinking ( Varoni et al, 2015 ), and chewing betel nut ( Su et al, 2020 ), and internal factors like gene mutation ( Ali et al, 2017 ), the human papillomavirus (HPV) ( Jiang and Dong, 2017 ), and abnormal gene expression also play a major role in the development of oral cancer. As a class of gene regulatory factors, lncRNA plays an important role in oral cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Reiter et al reported that AURKA upregulation promoted the disease stage, the occurrence of positive regional lymph nodes, and the level of distant metastasis, reducing the disease-free survival time and OS rate of patients [ 34 ]. Huang et al [ 35 ] indicated that the risk of oral cancer increased significantly among smokers with high AURKA expression, which had a certain reference value for screening groups at high risk for oral cancer. Yang et al [ 36 ] showed that MLN8237, an AURKA inhibitor, inhibited AURKA autophosphorylation at Thr288, leading to abnormal cell division and cell cycle to stop cell aging in the G2/M phase.…”
Section: Discussionmentioning
confidence: 99%